2017
DOI: 10.1371/journal.pone.0188829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food simulating liquids on the flexural strength of a methacrylate and silorane-based composite

Abstract: ObjectiveThe purpose of this study was to assess the effect of food-simulating liquids on the flexural strength of a methacrylate-based and a silorane-based resin composite.Materials and methodsIn this in vitro study, sixty specimens of Filtek P90 and Filtek Z350 composite were prepared in a customized mold (2 × 2 × 25 mm). The specimens of each composite were divided into five subgroups as follows: one as a control group and the other four groups included distilled water, heptane, 2% citric acid, and 50% aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
12
0
3
Order By: Relevance
“…The continuous temperature changes performed in thermocycling have an influence on the bonding materials, causing the resin to expand and contract, as its thermal expansion coefficient is higher than that of the teeth; the higher the thermal expansion coefficient of a resin, the worse it would be for the adhesive interface as volumetric changes of the resin will be greater. Moreover, the presence of water during this procedure causes hygroscopic expansion as well as chemical degradation of the resinous components, a process known as plastification (23). This deleterious effect of thermal changes and hydrolytic degradation has been more relevant for the first 10,000 cycles, without a significant decrease in SBS values when the number of cycles was doubled; similarly to what happened to Turk et al (21) who did not find any significant difference between 10,000 and 20,000 cycles for Transbond XT Light Cure Adhesive (3M Unitek).…”
Section: Discussionmentioning
confidence: 99%
“…The continuous temperature changes performed in thermocycling have an influence on the bonding materials, causing the resin to expand and contract, as its thermal expansion coefficient is higher than that of the teeth; the higher the thermal expansion coefficient of a resin, the worse it would be for the adhesive interface as volumetric changes of the resin will be greater. Moreover, the presence of water during this procedure causes hygroscopic expansion as well as chemical degradation of the resinous components, a process known as plastification (23). This deleterious effect of thermal changes and hydrolytic degradation has been more relevant for the first 10,000 cycles, without a significant decrease in SBS values when the number of cycles was doubled; similarly to what happened to Turk et al (21) who did not find any significant difference between 10,000 and 20,000 cycles for Transbond XT Light Cure Adhesive (3M Unitek).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that a composite material with a low modulus of elasticity when placed in stress-bearing areas suffered greater distortion and marginal deterioration under masticatory forces [8]. Several studies have reported the effects of food-like agents on the mechanical properties of dental composites [9,10], and the mechanical stability of bulk-fill restorations in stress-bearing areas remains a challenge to be addressed. Accordingly, the effects of food-simulating solvents on the flexural properties of bulk-fill composites must be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Water sorption in moderate amounts releases the internal stresses induced by polymerization shrinkage, compensates for the shrinkage, and consequently, improves the marginal seal. [13141516]…”
Section: Introductionmentioning
confidence: 99%